Comparison of metabolite profiles and bioactivities of three Ziziphus species - Ihsanul Hafiz, Muhamad Insanu, Nizar Happyana (Journal of Applied Pharmaceutical Science, 2025)
Ziziphus jujuba, Ziziphus spina-christi, and Ziziphus mauritiana, members of the Ziziphus genus, possess antioxidant activity and demonstrate potential as antidiabetic agents. In this study, 1H-NMR-based metabolomics was employed to evaluate metabolite profiles of the fruits, seeds, and leaves of Z. jujuba, Z. spina-christi, and Z. mauritiana. The inhibitory activities of the plant extracts were evaluated against α-glucosidase and dipeptidyl peptidase IV enzymes. The antioxidant activity of the plant extracts was also examined through the 1,1-diphenyl-2-picrylhydrazyl and cupric ion reducing antioxidant capacity methods. A total of 50 compounds were annotated putatively, comprising 41 known compounds and 9 unknown compounds. Bioactivity tests indicated that Z. mauritiana exhibited the highest potential as an antioxidant and enzyme inhibitor compared to the other two species, with its leaves displaying the most significant activity. Multivariate data analysis successfully classified and differentiated Ziziphus samples based on their components. Correlation analysis identified six compounds, including apigenin, catechin, kaempferol, quercetin, rutin, and oleic acid, as potential contributors to the antioxidant and α-glucosidase inhibitory activities of the Ziziphus samples. Our work provided a deeper understanding of the metabolite profiles of the three Ziziphus species and offered valuable knowledge for further investigation and potential applications in various health-related fields.
Keywords: Antioxidant, α-glucosidase inhibitors, DPP IV inhibitors, 1H NMR-based metabolomics, Ziziphus